Community Characteristics and Perception of Traditional Medicine Made from Herpetofauna in Jakarta and Bandung: KARAKTERISTIK DAN PERSEPSI MASYARAKAT TERHADAP OBAT TRADISIONAL BERBAHAN HERPETOFAUNA DI JAKARTA DAN BANDUNG - Hanny Herzegovina; Mirza D. Kusrini; Burhanuddin Masy'ud (Media Konservasi, 2019)
The research on herpetofauna to be used as traditional medicine are still few compared to research on medicinal plants, especially in Indonesia. This paper discusses the characteristics of traders and consumers of medicine that derived from herpetofauna and also examines the perceptions of traders and consumers on herpetofauna conservation and their use as medicine. To compare whether there are different perceptions between consumers in Jakarta and Bandung, the Chi square test was used; and to find out whether there are influence of education and age on respondents' perceptions, the Spearman test was used. The results showed that most traders were dominated by men of productive age with a relatively low level of education. The traders are mostly Moslem, and originated from Betawi and Sundanese. Most traders have been in the business for more than 20 years.The consumers are also dominated by men and fairly even between Moslems and non Moslems. Consumers are generally Chinese and most of them are aged 35-39. The level of education of consumers is higher than the traders. No significant differences were found regarding the perception of traders and consumers in the two cities. There is a significant positive correlation between education level and perceptions regarding animal use regulations and animal protection regulations. Keywords: characteristics, consumer, reptile, amphibian, medicine